Third person reference in Hong Lou Meng and its English translations / Zhang Yanan - Zhang, Yanan (2017)
The aim of this research, specifically, is to compare and contrast the different usages of third person references applied in the Chinese ST and in its two English TTs. The Chinese novel Hong Lou Meng and its two English versions entitled ‘A Dream of Red Mansions’ and ‘The Story of the Stone’ are used as main data for this current research. The sources which contain the third person reference found in the first three chapters of these three books were collected from both the original SL text of Hong Lou Meng in Chinese ST and the two translated TTs in English. One hundred and ninety-eight sentences including third person reference from the first three chapters of each book were extracted and coded to ease analysis. Halliday and Hasan’s (1976) taxonomy of third person reference was used to identify the different categories of third person reference. Besides, the different ways of translating third person references employed in the two English versions were also further explored according to Reiss and Vermeer’s (1984) Skopos theory. Findings of this study reveal that the numbers and types of third person reference found in the Hong Lou Meng and its two English translations are shown differently. Furthermore, this study also indicated that the two translators of Hong Lou Meng have different Skopos and translating style. The way of translating third person references in the two target contexts was construed differently based on their own translated version of Skopos as well as their Chinese or Western cultural influence. As a result, the analyzed data has shown that the level of TT’s explicitness is much higher than that of ST’s, and the level of T2’s explicitness is even higher than that of T1’s.